Revisiting Electoral Violence in Zimbabwe: Problems and Prospects - Tirivangasi, Happy Mathew; Nyahunda, Louis; Maramura, Tafadzwa Clementine (International Journal of Criminology and Sociology, 2021)
This study explores theoretical contradictions with realism, regarding the actors or perpetrators of violence when explaining the causes of electoral violence in the Zimbabwean context. These perspectives can be divided into two contesting schools of thought. The first group is mainly made up of rational theories and holds the position that, autocratic governments use electoral violence as a way of influencing electoral outcome. The second position suggests that the weaker political party is the one responsible for electoral violence. This paper then, contributes to the ongoing debate on the causes of electoral violence by advancing the notion that electoral violence should not be seen based on one position but from a multifaceted position. This is because, neither of the two theoretical approaches are wrong but what differs is the context. This paper argues that the idealism of holding one position hinders policy analysis to electoral violence, monitoring and observing election process as it places either, the ruling party or the opposition party as a unit of analysis.